Frequency of Vitamin a Deficiency in Children Hospitalized for Pneumonia: An Integrative Review - Amanda De Conceição Leão Mendes; Ana Mayara Gomes De Souza; Aryelly Dayane Da Silva Nunes; Javier Jerez-Roig; Isabelle Ribeiro Barbosa (Frontiers Media S.A., 2022)
Objective: To identify the frequency of vitamin A deficiency in children aged 6 months to 5 years hospitalized for pneumonia.Methods: An integrative literature review was carried out, where searches were made by two independent researchers, with no language limits or publication time in the databases PubMed, LILACS, Web of Science, Scopus and CINAHL, and in the gray literature-OpenGrey, Proquest and Google Scholar. In the eligibility phase, the screened studies were read in full and those that did not answer the research question were excluded. Methodological quality was assessed using the Downs & Black (1998) checklist.Results: 1642 articles were identified, after all stages of screening and selection, 10 studies were included, of which 5 were longitudinal, 4 were intervention and 1 transversal. All studies identified subclinical vitamin A deficiency in children hospitalized with pneumonia; the highest frequency of subclinical vitamin A deficiency was 93.2%. All studies evaluated showed frequencies of subclinical vitamin A deficiency >20%.Conclusion: There is a high frequency of subclinical vitamin A deficiency in children with pneumonia; these data need to be further explored in terms of their associations. For this reason, new studies that evaluate this topic are of fundamental importance.